Mathematical simulation of the stress-strain state of the winding of a closed magnetic system - Martynov, S.O.; Lukyanova, V.P.; Prokhorets, S.I.; Yurkin, A.Yu.; Khazhmuradov, M.A. (Problems of Atomic Science and Technology, 2022)
Mathematical modeling of the stress-strain state of the winding of a closed magnetic system was carried out, which consists in the development of a three-dimensional geometric model of the helical winding and the determination of the values of the characteristics of the magnetic system, which are best from the point of view of meeting the requirements of the technical task of the designed object.